Intense Hurricane Activity Over the Past 1500 Years at South Andros Island, The Bahamas. Issue 11 (27th November 2019) - Wallace, E. J.; Donnelly, J. P.; van Hengstum, P. J.; Wiman, C.; Sullivan, R. M.; Winkler, T. S.; d'Entremont, N. E.; Toomey, M.; Albury, N.
Abstract: Hurricanes cause substantial loss of life and resources in coastal areas. Unfortunately, historical hurricane records are too short and incomplete to capture hurricane‐climate interactions on multi‐decadal and longer timescales. Coarse‐grained, hurricane‐induced deposits preserved in blue holes in the Caribbean can provide records of past hurricane activity extending back thousands of years. Here we present a high resolution record of intense hurricane events over the past 1500 years from a blue hole on South Andros Island on the Great Bahama Bank. This record is corroborated by shorter reconstructions from cores collected at two nearby blue holes. The record contains coarse‐grained event deposits attributable to known historical hurricane strikes within age uncertainties. Over the past 1500 years, South Andros shows evidence of four active periods of hurricane activity. None of these active intervals occurred in the past 163 years. We suggest that Intertropical Convergence Zone position modulates hurricane activity on the island based on a correlation with Cariaco Basin titanium concentrations. An anomalous gap in activity on South Andros Island in the early 13th century corresponds to a period of increased volcanism. The patterns of hurricane activity reconstructed from South Andros Island closely match those from the northeastern Gulf of Mexico but are anti‐phased with records from New England. We suggest that either changes in local environmental conditions (e.g., SSTs) or a northeastward shift in storm tracks can account for the increased activity in the western North Atlantic when the Gulf of Mexico and southeastern Caribbean are less active. Key Points: Sediment cores from blue holes on Andros Island record intense hurricane activity over the past millennium and a half Multi‐decadal shifts in Intertropical Convergence Zone position and volcanic activity modulate the hurricane patterns observed on Andros Hurricane patterns on Andros match patterns from the northeastern Gulf of Mexico but are anti‐phased with patterns from New England